2019
DOI: 10.1111/1462-2920.14698
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the sterigmatocystin secondary metabolite gene cluster in the filamentous fungus Podospora anserina: involvement in oxidative stress response, sexual development, pigmentation and interspecific competitions

Abstract: Summary Filamentous fungi are known as prolific untapped reservoirs of diverse secondary metabolites, where genes required for their synthesis are organized in clusters. The bioactive properties of these compounds are closely related to their functions in fungal biology, which are not well understood. In this study, we focused on the Podospora anserina gene cluster responsible for the biosynthesis of sterigmatocystin (ST). Deletion of the PaStcA gene encoding the polyketide synthase and overexpression (OE) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 75 publications
2
48
0
Order By: Relevance
“…Correspondingly, the deletion of PaSNF1 led to a defect in perithecium production and ascospore formation. Moreover, OE-PaAflR displayed overproduction of ST, and overexpression of PaAflR also led to sterility (Shen et al, 2019). These results indicated that ST was closely related to the development of fungi and spore formation.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Correspondingly, the deletion of PaSNF1 led to a defect in perithecium production and ascospore formation. Moreover, OE-PaAflR displayed overproduction of ST, and overexpression of PaAflR also led to sterility (Shen et al, 2019). These results indicated that ST was closely related to the development of fungi and spore formation.…”
Section: Discussionmentioning
confidence: 78%
“…Recent studies have shown that ABR1 was involved in biosynthesis of DHN melanin, which colored ascospores; and knockout of ABR1 led to decreased ascospore pigmentation accompanied by lowered ascospore germination rate (Xie et al, 2018). Shen et al (2019) reported that PaStcA and PaAflR were key genes necessary for the biosynthesis of ST in P. anserina, deletion of PaStcA that blocked the ST pathway, and overexpression of PaAflR that resulted in the excessive accumulation of ST, thus leading to a female sterility phenotype. In this study, to identify the metabolites regulated by PaSNF1, the large-scale fermentation of the PaSNF1 mutant was performed, and the structures of metabolites with unique peaks were characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, oxidative stress seems to have been a key player in the evolution of fungal secondary metabolism (Roze et al ., 2011; Montibus et al ., 2015). In fact, stimulation of SMs formation by oxidative stress and ROS formation has recently been reported in several fungi, such as aflatoxin production by A. parasiticus , ochratoxin A formation by A. ochraceus , deoxynivalenol formation by F. graminearum and sterigmatocystin formation in Podospora anserina (Jayashree and Subramanyam, 2000; Reverberi et al ., 2012; Chen et al ., 2019; Shen et al ., 2019). In P. anserina , SMs were considered to function as a supplemental source of antioxidant protection, which enhance stress tolerance along with antioxidant enzyme gene expression (Shen et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, mining of the P. anserina genome revealed a large number of putative biosynthetic gene clusters (BGCs) for secondary metabolites ( 11 ). However, to date, only very few products that exhibited antibacterial, antifungal, and larvicidal activities have been characterized in this species during past decades ( 12 14 ), probably because most BGCs are silent under standard culture conditions ( 10 , 15 ). Genomics-driven BGC detection and preliminary chemical investigations so far imply that P. anserina is a prolific, as-yet unexploited natural product reservoir.…”
Section: Introductionmentioning
confidence: 99%